ESTETIKA TARI SANDUR RONGGO BUDOYO TUBAN PADA ACARA SEDEKAH BUMI OLEH SISWA SMP NEGERI 3 TUBAN - saputra, joko; yanuartuti, Setyo; sabri, indar; Juwariyah, Anik (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
This study discusses the aesthetics of the Sandur Ronggo Budoyo Tuban Dance in the performance of the earth alms event by students of SMPN 3 Tuban. The Sandur dance is one of the traditional dances of the intangible cultural heritage of Tuban regency which has aesthetic value, beauty of movement, and symbolic meaning. This research aims to analyze the aesthetic elements contained in the dance, including aspects of movement, accompanying music, costumes, and expression abilities that represent cultural identity by the santur dancers, providing added value in maintaining and introducing local culture to the younger generation. This study uses a qualitative method with direct observation and interviews with art actors, dance coaches, dancers and performance documentation. The performance of SMPN 3 Tuban students succeeded in displaying the beauty and uniqueness of the Sandur Ronggo Budoyo Dance. The values contained include the values of ethics, please help and tolerance